A modification of Faddeev-Popov approach free from Gribov ambiguity - Chen, Chong-yao; Gao, Fei; Liu, Yu-Xin (Communications in theoretical physics, 2020)
We propose a modified version of the Faddeev-Popov (FP) quantization approach for non-Abelian gauge field theory to avoid Gribov ambiguity. We show that by means of introducing a new method of inserting the correct identity into the Yang-Mills generating functional and considering the identity generated by an integral through a subgroup of the gauge group, the problem of Gribov ambiguity can be removed naturally. Meanwhile by handling the absolute value of the FP determinant with the method introduced by Williams and collaborators, we lift the Jacobian determinant together with the absolute value and obtain a local
Gesehen am 21.12.2020